Sjovold Site : A River Crossing Campsite in the Northern Plains - Dyck, Ian G. (Book collections on Project MUSE., 1995)
"Compared to the spectacular bison-kill sites for which the Plains region is justifiably famous, relatively little is known about the more ordinary aspects of ancient everyday life. Where did people make their homes? Why were particular sites chosen? Who might occupy a given camp and how long might they stay? What activities were carried out? The Sjovold site, situated on the west bank of the South Saskatchewan River in the far northern Plains, offers a long and detailed archaeological record with which to address these questions. People camped here more than twenty times over a period of 3,200 years, from 1850 B.C. to A.D. 1350. This book describes and interprets the findings from excavations of each encampment through this long sequence." "Locally, the Sjovold site offered shelter from the prevailing winds and access to the rich resources of a wooded creek valley. More generally, it seems to have been near the boundary between two vegetation zones: the grasslands and the aspen parklands. It is also near the Missouri Coteau, a long line of broken hills used historically as a war road. Perhaps more important, however, is its proximity to one of the few good river crossings in the region. This study specifies the criteria for defining and recognizing a river crossing campsite. It also explores many features of life in ancient times, inferring, along with the cultural and historical framework, societal dimensions such as group size and gender, trade and travel, as well as a wide variety of daily activities."--Jacket